Mole-rats Nannospalax leucodon and Spalax zemni in Ukraine: identification criteria and border between their ranges - Zagorodniuk, I.; Korobchenko, M.; Kirichenko, V. (Праці теріологічної школи, 2017)
The differences between two mole-rat species are shown according to the complex of exterior and cranial characters, each of which is reliable in species diagnostics. In particular, they include the color of rhinarium, shape of the rostrum, development of lateral occipital apertures and pharyngeal tubules, also the flexion of the base of the skull, and expressiveness of the intercrestal fossa in the mandible. A number of collection materials were re-identified, which significantly changed the views on geographical ranges of these species. The boundary between species should be considered substantially shifted to the west: the Bug–Tylihul interriver area is inhabited not by N. leucodon, as it was believed so far, but by S. zemni. It is confirmed by both old specimens (1930–1950s) and modern materials (2010–2016), thus it is not associated with habitat changes. At the same time, monitoring of the dynamics of settlements of these species shows significant changes in the scope of inhabited areas, as well as recent colonization of the most part of the region from coastal refugia. Показано відмінності двох видів сліпаків за комплексом екстер’єрних та краніальних ознак, кожна з яких є надійною в діагностиці видів, зокрема за кольором ринарію, формою рострума, розвитком бічних потиличних отворів, глоткових горбків та зламу основи черепа, виразністю на мандибулі міжгребеневої ямки. Перевизначено низку колекційних матеріалів, які суттєво змінили уявлення про ареали цих видів. Відома в літературі межа між видами суттєво зміщена на захід: у межиріччі Бугу та Тилігулу мешкає не N. leucodon, як вважали дотепер, а S. zemni. Це підтверджують як давні зразки (1930–1950-х рр.), так і сучасні матеріали (2010–2016 рр.), тобто це не пов’язано зі змінами ареалів. У той же час спостереження за динамікою поселень цих видів засвідчують суттєві зміни в обсягах заселених ними територій і недавнє заселення ними більшої частини регіону з приморських рефугіумів.